Sustainable Development and Justice between Generations in Latvia. Case of IT Professionals - Gribanova Svetlana (E3S Web of Conferences, 2021)
The ideas of social justice between members of the same generation and between members of different generations are described in scientific literature as the main normative principles of sustainable development. Distribution of public resources between generations can be considered fair and honest, when each successive generation can expect the same care and benefits as the previous generation. But, in the modern world, it is almost impossible. Are there any intergenerational conflicts in Latvia connected with environmental and social justice? This question has become the main research issue of this study. The results of the study show that in Latvian society there is a certain understanding of environmental justice, as necessity to limit intensity of consumption in order to preserve the environment. In this issue, interests of all generations intersect, so environmental problems can be solved in society without intergenerational conflicts. Social justice issues are more complex for Latvian society. Even in high-income social groups, generational perceptions of how fairly the state redistributes public resources differ. This provokes a protest, which is expressed in unwillingness to pay taxes and justification of tax evasion.